Hubungan Tingkat Stres Dengan Hipertensi Sebagai Dasar Upaya Promotif Dan Preventif Di Klinik Dandy Dinda Tembung - Tarianna Ginting; Eltri Erisa Br Lingga; Ellya Sibagaring (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Hypertension remains a major non-communicable disease and a public health concern in Indonesia, with psychological stress recognised as an important modifiable risk factor. This study aimed to analyse the association between stress level, promotive efforts, and preventive efforts with the incidence of hypertension at Dandy Dinda Clinic, Tembung. A quantitative observational study with a cross-sectional design was conducted from May to June 2026. The population consisted of 107 hypertensive patients recorded between January and May 2026, and 84 respondents were selected using the Slovin formula with a 5% margin of error. Primary data were collected through structured questionnaires, including the Perceived Stress Scale (PSS-10), while secondary data were obtained from clinic records. Data were analysed using univariate distribution and the Chi-Square test at a 95% confidence level. The results showed that most respondents experienced moderate stress (59.5%) and stage 1 hypertension (61.9%). The Chi-Square test indicated a significant association between stress level and hypertension (p=0.006), promotive efforts and hypertension (p=0.024), and preventive efforts and hypertension (p=0.009). These findings suggest that stress management, health education, and preventive behaviours should be strengthened at the primary care level to support hypertension control.